Does municipal incorporation always increase property values?. (5th November 2021) - Hodges, Collin D.; Stephens, Heather M.
Abstract: Municipal formation by voter approval should reflect the costs and benefits associated with the more localized control and provision of public services. To the extent that the benefits associated with incorporation exceed the costs, the impact of a new municipal formation should be positively capitalized into housing values within the new municipality. However, differences in local policy, municipal characteristics, and voter sentiment may impact rates of capitalization. Using housing transactions data from 2000 to 2014, we investigate the impact of four new municipal incorporations on housing values in Riverside County, California. We find that, in contrast to previous studies in other regions, there is a generally negative capitalization effect observed post‐incorporation in the new cities of Riverside County. Our results are robust to multiple model and matching specifications and suggest that not all housing markets respond the same to incorporation and that heterogeneity in regional policies and local characteristics are important to understanding how incorporation will impact a community.